(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2024)
Ethiopia has favorable climate conditions for the production of spices, herbs, aromatic and medicinal plants useful for flavoring food, aroma, therapeutic and marketing for cash income. Ethiopian is the largest consumer of spices in Africa, but the contribution of spice to the national economy is meager. The study area is endowed with diversified spice types with different purposes. However, it is not well announced, attention is not given and still many spices are growing in the wild. However, it is not well announced, attention is not given, and many spices are still collected from the wild. This study aimed to assess spice production and marketing in Kaffa biosphere reserve. This study was undertaken in four districts of Kaffa zone including Tello, Gimbo, Shishoende and Decha districts by selecting one representative kebele from each district. The data collection method used for this study is a household survey, key informant interviews and focus group discussion. Out of the total sampled 89% of sampled households participate and produce diversified types of spice. Korarima, red pepper, rue, ginger, turmeric, bush tea, holey basil, machewolago, aemacho nechamacho, coriander, rosemary, onion, long pepper and lemon grass were identified at the household survey. About 60.9% of the sample households provide spice products to market and the sample households generate a mean income of 1,611.14 ETB from spice product marketing. Most sampled households ranked themselves at low and very low knowledge levels on spice production and marketing. Spices are mainly produced in the home garden area for consumption. The main challenges for spice production in the study area are the unavailability of improved variety, low attention given by government and stakeholders, unavailability of the market, lack of knowledge and skill on production and post-harvest handling, low-value addition practice and unavailability of recommended practice. Creating a market for spice products and promotion is needed its importance and give attention to spice production. Training is needed for the farming community on spice cultivation, management, post-harvest handling and processing. Int. J. Agril. Res. Innov. Tech. 13(2): 22-30, Dec 2023